Low-stress sampling and cortisol measurements in periparturient sows - Goering, Mikayla J.; Mumm, Jared M.; Coffin, Morgan J.; Bortoluzzi, Eduarda M.; Ruiz, Luke A.; Hulbert, Lindsey E. (My University, 2017)
The most common method of cortisol sample collection for sows is jugular venipuncture, which requires restraint via snaring. Snaring can be an added stressor to sows, especially during the periparturient phase, when cortisol concentrations are already elevated and variable responses are expected. Therefore, the objectives of this study were to determine the variation of stress-responses to farrowing using less-invasive sample collection methods (saliva vs. low-volume ear vein blood). Samples were collected from 10 multiparous sows (DNA Genetics; K-State Swine Research Center) at -1 and +1 d relative to farrowing. Sows were offered a 51 cm cotton-rope to chew on and 300 uL of blood was drawn after ear venipuncture using a 26 gauge needle and syringe treated with heparin. After centrifugation, saliva and plasma were harvested from solid-particles and blood cells then immediately frozen at -20°C until cortisol concentration analysis using a commercially available ELISA kit (Detect X Cortisol Assay; Arbor Assays, Anne Arbor, MI). Sows tended, (P = 0.06) to have less ear-vein plasma cortisol concentrations at -1 than +1 d relative to parturition but differences in cortisol concentrations were not detected from saliva samples (P = 0.67). The range of cortisol concentration was greater in the plasma-samples than the salivary samples (19.17 to 55.50 vs. 0.69 to 6.14 ng/mL, respectively). Nonetheless, CV% was lower among plasma than salivary samples (24.8 vs. 67.3%). If a treatment is expected to cause a 25% change in cortisol secretion, then only 21 sows will be needed per treatment if plasma is measured, whereas 152 pigs will be needed if saliva is measured. Therefore, the preferred sample collection method for future experiments involving periparturient sows will be ear-venipuncture, rather than salivary collection.
Keywords: Fall 2017